Data science from scratch : first principles with Python - Grus, Joel (Sebastopol, California : O'Reilly Media, Incorporated, 2015)
To really learn data science, you should not only master the tools$1 (Bdata science libraries, frameworks, modules, and toolkits$1 (Bbut also understand the ideas and principles underlying them. Updated for Python 3.6, this second edition of Data Science from Scratch shows you how these tools and algorithms work by implementing them from scratch. If you have an aptitude for mathematics and some programming skills, author Joel Grus will help you get comfortable with the math and statistics at the core of data science, and with the hacking skills you need to get started as a data scientist. Packed with New material on deep learning, statistics, and natural language processing, this updated book shows you how to find the gems in today$1 (Bs messy glut of data.s
1. Introduction -- 2. A crash course in Python -- 3. Visualizing data -- 4. Linear algebra -- 5. Statistics -- 6. Probability -- 7. Hypothesis and inference -- 8. Gradient descent -- 9. Getting data -- 10. Working with data -- 11. Machine learning -- 12. k-Nearest neighbors -- 13. Naive Bayes -- 14. Simple linear regression -- 15. Multiple regression -- 16. Logistic regression -- 17. Decision trees -- 18. Neural networks -- 19. Clustering -- 20. Natural Language Processing -- 21. Network analysis -- 22. Recommender systems -- 23. Databases and SQL -- 24. MapReduce -- 25. Go forth and do data science.
Includes bibliographical references and index.
Keywords: PYTHON (COMPUTER PROGRAM LANGUAGE)